Vacuum annealed Ga:ZnO (GZO) thin films for solar cell integrated transparent antenna application - Alobaidi O.R.; Chelvanathan P.; Bais B.; Sopian K.; Alghoul M.A.; Akhtaruzzaman M.; Amin N. (Elsevier B.V., 2023)
Annealing; Electric conductivity; Energy gap; II-VI semiconductors; Microstrip antennas; Optical films; Slot antennas; Solar cells; Zinc oxide; Active material; Antenna applications; Electrical conductivity; Ga-doped ZnO; Satellite networking; Thin-films; Transparent antenna; Transparent conductive oxide; Windows Embedded; ZnO thin film; Thin films